Determination of arbutin in vitro and in vivo by LC-MS/MS: Pre-clinical evaluation of natural product arbutin for its early medicinal properties. - Wang, Qiao-Lai; Zhang, Pei-Xi; Shen, Rui; Xu, Meng; Han, Liang; Shi, Xuan; Zhou, Zi-Rui; Yang, Jing-Yi; Liu, Jie-Qing (Journal of Ethnopharmacology, 2024)
Arbutin is a naturally occurring glucoside extracted from plants, known for its antioxidant and tyrosinase inhibiting properties. It is widely used in cosmetic and pharmaceutical industries. With in-depth study of arbutin, its application in disease treatment is expanding, presenting promising development prospects. However, reports on the metabolic stability, plasma protein binding rate, and pharmacokinetic properties of arbutin are scarce. The aim of this study is to enrich the data of metabolic stability and pharmacokinetics of arbutin through the early pre-clinical evaluation, thereby providing some experimental basis for advancing arbutin into clinical research. We developed an efficient and rapid liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay for determining arbutin in plasma. We investigated the metabolic and pharmacokinetic properties of arbutin through in vitro metabolism assay, cytochrome enzymes P450 (CYP450) inhibition studies, plasma protein binding rate analysis, Caco-2 cell permeability tests, and rat pharmacokinetics to understand its in vivo performance. In vitro studies show that arbutin is stable, albeit with some species differences. It exhibits low plasma protein binding (35.35 ± 11.03% ∼ 40.25 ± 2.47%), low lipophilicity, low permeability, short half-life (0.42 ± 0.30 h) and high oral bioavailability (65 ± 11.6%). Arbutin is primarily found in the liver and kidneys and is eliminated in the urine. It does not significantly inhibit CYP450 up to 10 μM, suggesting a low potential for drug interactions. Futhermore, preliminary toxicological experiments indicate arbutin's safety, supporting its potential as a therapeutic agent. This study provides a comprehensive analysis the drug metabolism and pharmacokinetics (DMPK) of arbutin, enriching our understanding of its metabolism stability and pharmacokinetics properties, It establishes a foundation for further structural optimization, pharmacological studies, and the clinical development of arbutin. [Display omitted] • A rapid and efficient LC-MS/MS assay for the determination of Arbutin has been developed. • Enrichment of drug metabolism and pharmacokinetics data for Arbutin. • The pharmacokinetic properties of arbutin and the factors that influence them were investigated. • Preparation of arbutin for entry into clinical development.